2019
DOI: 10.1039/c9tc01658a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel nonlinear optical chromophores with enhanced electro-optic activity by introducing suitable isolation groups into the donor and bridge

Abstract: Four nonlinear optical chromophores A–D functionalized with different isolation groups on both the donor and bridge sections of the chromophores have been synthesized and systematically investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Similar to many NIR dipolar polyenes, merocyanines, and cyanines, the meso -substituted oxazolyl thiother groups provide the sulfur’s π-accepting interaction with the conjugated structures of new push–pull heptamethines. Herein, the primary π-accepting orbital of sulfur is associated with its low-lying sigma antibonding orbital, enabling negative hyperconjugation from the linked carbon p π orbital to the antibonding orbital σ* S–C of the sulfur–carbon bond. The NMR spectra showed that two olefinic protons H b and H c neighboring the sulfur atom in new heptamethine chromophores experience significant deshielding of chemical shifts (0.37–0.53 ppm) compared to the corresponding protons in meso -chloro-substituted chromophores (Table S1).…”
Section: Resultsand Discussionmentioning
confidence: 99%
“…Similar to many NIR dipolar polyenes, merocyanines, and cyanines, the meso -substituted oxazolyl thiother groups provide the sulfur’s π-accepting interaction with the conjugated structures of new push–pull heptamethines. Herein, the primary π-accepting orbital of sulfur is associated with its low-lying sigma antibonding orbital, enabling negative hyperconjugation from the linked carbon p π orbital to the antibonding orbital σ* S–C of the sulfur–carbon bond. The NMR spectra showed that two olefinic protons H b and H c neighboring the sulfur atom in new heptamethine chromophores experience significant deshielding of chemical shifts (0.37–0.53 ppm) compared to the corresponding protons in meso -chloro-substituted chromophores (Table S1).…”
Section: Resultsand Discussionmentioning
confidence: 99%
“…The latter threshold can be overcome by switching to more recent nonlinear materials. New organic materials have been shown to work under much higher temperatures 46,47 . Also, recent barium titanate (BTO) plasmonic modulators have shown great potential for high-power applications with demonstrated high-temperature stability beyond 250 °C 48 .…”
Section: Methodsmentioning
confidence: 99%
“…[34][35][36] In past a decade, EO performance has been improved via strategies such as siteisolation, self-assembly, chromophore blending, and charge blocking layers (CBLs) to enhance the r N hcos 3 yi value of bulk materials. 26,28,31,33,[37][38][39][40][41][42][43][44][45][46][47][48][49] Recent work 50,51 has also shown substantial increases in hyperpolarizability due to theoryguided design, after years of little increase in b of reported chromophores.…”
Section: Introductionmentioning
confidence: 99%